2017
DOI: 10.1590/0104-6632.20170341s20150475
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Techniques Applied to Lignocellulosic Ethanol in Simultaneous Hydrolysis and Fermentation

Abstract: This paper investigates the use of machine learning (ML) techniques to study the effect of different process conditions on ethanol production from lignocellulosic sugarcane bagasse biomass using S. cerevisiae in a simultaneous hydrolysis and fermentation (SHF) process. The effects of temperature, enzyme concentration, biomass load, inoculum size and time were investigated using artificial neural networks, a C5.0 classification tree and random forest algorithms. The optimization of ethanol production was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Research, Society and Development, v. 10, n. 6, e40410613705, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.13705 The sugarcane bagasse used contained about 50% water, 30% cellulose, 7.3% hemicellulose, 11.2% lignin and 1.5% ash, according to previous characterization (method according to Browning (1967). The use of biomass as a carbon source for cultivation of microorganisms in solid media and production of enzymes and biomass for cellulolytic ethanol have been highlighted in previous studies (Fischer et al, 2017;Lopes et al, 2017). The results obtained in the present study point to biomass, roasting and ground coffee residue (RGCR), still little used in technologies for obtaining cellulolytic enzymes and renewable energy.…”
Section: Selection Of Solid-state Fermentation Medium For Cec Productionmentioning
confidence: 58%
See 2 more Smart Citations
“…Research, Society and Development, v. 10, n. 6, e40410613705, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.13705 The sugarcane bagasse used contained about 50% water, 30% cellulose, 7.3% hemicellulose, 11.2% lignin and 1.5% ash, according to previous characterization (method according to Browning (1967). The use of biomass as a carbon source for cultivation of microorganisms in solid media and production of enzymes and biomass for cellulolytic ethanol have been highlighted in previous studies (Fischer et al, 2017;Lopes et al, 2017). The results obtained in the present study point to biomass, roasting and ground coffee residue (RGCR), still little used in technologies for obtaining cellulolytic enzymes and renewable energy.…”
Section: Selection Of Solid-state Fermentation Medium For Cec Productionmentioning
confidence: 58%
“…SSF cell concentrations were determined in a Neubauer Chamber. Propagation plate methodology (48 h incubation at 40 °C in Czapek medium) (Fischer et al, 2017) was sued to start SSF by estimating the optical density at 600 nm, correlated with the number of colonies obtained. The cellulase activity was determined by filter paper activity (FPA), following IUPAC standard procedures; result was expressed in international Units (Ghose, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the SHF process gave a higher concentration of ethanol (8.11 g•L −1 ). Fischer and others [33], in their research, dealt with lignocellulosic biomass and examined the SHF process, obtaining the ethanol concentration of 12.1 g•L −1 . SHF as an alternative process in an industrial bioethanol plant manifests both potential and limitations.…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%
“…To improve prediction performance, in this study, we developed ensemble machine learning (ML) models and applied them on this first dataset obtained from feedstocks available in Florida (dataset 1). Although ML has been widely adopted in many fields of research, including other bio-related fields [15][16][17], there have been very few applications of ML in deconstruction studies involving either a single or multiple feedstocks [18][19][20]. In this study, we tested the application of ML models such as single regression and 2-fold ensemble models integrated with four base learners in linear-weighted regression and nonlinear stochastic gradient boosting models (gbm).…”
Section: Introductionmentioning
confidence: 99%